Beyond Pills: Synergizing Pharmacological and Physical Activity Interventions in Fibromyalgia Treatment. A review - Bochenek, Oliwia; Koper, Mateusz; Nowak, Aleksandra; Kałuża, Jessica; Konaszczuk, Adrian; Ratyna, Klaudia; Kozyra, Oliwia; Szypuła, Zofia; Paluch, Katarzyna; Skarbek, Małgorzata (Quality in Sport, 2024)
Introduction and purpose Fibromyalgia (FM) is a chronic condition characterized by widespread musculoskeletal pain, fatigue, sleep disturbances, and cognitive impairment, affecting 2-4% of the global population, with a higher prevalence among women and those of lower socioeconomic status. The pathogenesis of FM is complex and multifactorial, involving central sensitization and neurochemical dysregulation. This review highlights the latest advancements in pharmacological and behavioral therapies for fibromyalgia. State of knowledge Management of fibromyalgia currently is based on a combination of medication use and non-pharmacological approaches, primarily based on physical activity and cognitive-behavioral therapy. This review explores advancements in FM treatments, focusing on novel pharmacological agents such as vortioxetine, eslicarbazepine acetate, and tapentadol, which target specific neurochemical pathways to alleviate symptoms. Vortioxetine offers new mechanisms of action with potential cognitive benefits, while eslicarbazepine acetate and tapentadol provide alternative approaches for pain modulation and central sensitization. Additionally, non-pharmacological therapies, including high-intensity interval training (HIIT) and virtual reality (VR) therapy, demonstrate promise in enhancing physical fitness, reducing pain, and improving quality of life for FM patients. Summary Overall, the integration of these novel therapies into comprehensive, individualized treatment plans can optimize outcomes and enhance the quality of life for individuals with FM. Ongoing research and personalized medicine approaches are essential to further refine and validate these emerging treatments.